How to design food, land and water policies to address hunger and climate change in today’s political economy - Mockshell, Jonathan; Resnick, Danielle (2023)
Political Economy and Policy Analysis (PEPA) sourcebook set out how governments can make use of a step-by-step guide to account for power dynamics, conflicting interests, coalitions and networks when developing agri-food policies. The book draws upon dozens of frameworks and tools to support policy development that addresses the dual challenges of food security and climate change.